Integrated in-package treatment of hydrogen peroxide and cold plasma for microbial inactivation of cabbage slices - Kim, Ye Eun; Myung, Ga Eun; Jeon, Ye Jeong; Min, Sea C. (Food science and biotechnology, 2024)
The efficacy of an in-package microbial inactivation method, combining H 2 O 2 and atmospheric dielectric barrier discharge cold plasma (ADCP) treatments (H 2 O 2 -ADCP), in reducing contamination of Brassica oleracea (cabbage) slices was investigated. Cabbage slices were placed in a polyethylene terephthalate container with a H 2 O 2 -soaked polypropylene pad attached to the inside of the lid, followed by subjecting the closed container to ADCP treatment. The H 2 O 2 -ADCP treatment inactivated Escherichia coli O157:H7 and Listeria monocytogenes , resulting in reductions of 1.8 and 2.0 log CFU/g, respectively, which were greater than the sum of the inactivation effects observed with each individual treatment. The combined treatment decreased the count of Bacillus cereus spores and indigenous bacteria by 1.0 log spores/g and 1.3 log CFU/g, respectively. Moreover, the in-package method did not alter the moisture content or texture of cabbage slices. These results demonstrate the potential of H 2 O 2 -ADCP as a microbial decontamination method for packaged cabbage slices.